Students Problems in Writing Paraphrases in Research Paper Writing Class - Hayuningrum, Herdiansari; Yulia, Made Frida (English Education Study Programme of Sanata Dharma University, Yogyakarta, Indonesia, 2012)
Paraphrase is one of the techniques of incorporating sources in which every writer is allowed to borrow the authors ideas and restate them into their own words. Based on the previous study, it was found that English Language Education Study Program (ELESP) students, Sanata Dharma University, were unable to paraphrase properly since they tended to copy the authors words directly. If this problem was continuously ignored, it would be dangerous for the students because they could be charged with inadvertent plagiarism. This study was intended to investigate ELESP students problems in writing paraphrases and the reasons why they produce unacceptable paraphrases by conducting document analysis and interview in Research Paper Writing class. From the findings, it could be identified that the most frequent type of problem encountered by the students was word-for-word plagiarism.